2021
DOI: 10.1097/aco.0000000000001012
|View full text |Cite
|
Sign up to set email alerts
|

Patient monitoring in the nonoperating room anesthesia (NORA) setting: current advances in technology

Abstract: Purpose of reviewNonoperating room anesthesia (NORA) procedures continue to increase in type and complexity as procedural medicine makes technical advances. Patients presenting for NORA procedures are also older and sicker than ever. Commensurate with the requirements of procedural medicine, anesthetic monitoring must meet the American Society of Anesthesiologists standards for basic monitoring. Recent findingsThere have been improvements in the required monitors that are used for intraoperative patient care. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 68 publications
0
1
0
Order By: Relevance
“…In some cases, providers and patients may not even be in the same room. Although novel monitoring systems may assist providers, vigilance remains paramount [16,17]. Combining ergonomic limitations with sicker patients, it is no surprise that Schroeck et al [18 && ] found that NORA anesthesia providers report higher stress, workload, and anxiety.…”
Section: Nonoperating Room Anesthesia Difficultiesmentioning
confidence: 99%
“…In some cases, providers and patients may not even be in the same room. Although novel monitoring systems may assist providers, vigilance remains paramount [16,17]. Combining ergonomic limitations with sicker patients, it is no surprise that Schroeck et al [18 && ] found that NORA anesthesia providers report higher stress, workload, and anxiety.…”
Section: Nonoperating Room Anesthesia Difficultiesmentioning
confidence: 99%